Effects of phenylalanine on the liquid-expanded and liquid-condensed states of phosphatidylcholine monolayers - Cutró, Andrea Carmen (2019)
Background: Phenylalanine (Phe) is involved in physiological and pathological processes in cell membranes in which expanded and condensed states coexist. In this direction, it was reported that surface hydration is important for the binding affinity of the amino acid which significantly perturbs 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) monolayer structure and morphology. A deeper insight showed that Phe inserts in DPPC monolayer defects as a monomer at pH 5 and forms aggregates that adsorb to the membrane surface generating a reconfiguration of the lipid arrangement in areas of higher packing. This new arrangement in the monolayer causes the reorientation of dipoles of lipid and water molecules which is congruent with the dehydration and surface tension changes reported above. With this background, this article studies the affinity of Phe in liquid-expanded 1,2-dimyristoyl-sn-glycero-3 phosphocholine (LE DMPC) and liquid-condensed 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (LC DPPC) monolayers and their effects on membrane properties. Results: The adsorption of Phe can be described by a cooperative process in non-independent sites suggesting that Phe/lipid systems reorganize to form new structures at a high degree of coverage. Compressibility modulus and Brewster angle microscopy (BAM) images allow to propose that Phe causes a new phase in 1,2-dimyristoyl-sn-glycero-3 phosphocholine (DMPC) and DPPC. Conclusions: Phe imposes new arrangements in the lipid phase to form new structures with different compressibility behavior than lipid binary mixtures of DMPC and DPPC. Phe interaction with the LC and LE phases gives place to a process in which a synergistic effect between non-independent sites can be produced. These features of Phe/lipid interaction would be of great importance to understand the multiple effects of Phe on cell membranes.